2018
DOI: 10.1002/hyp.13358
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulics of overland flow influenced by litter incorporation under extreme rainfall

Abstract: Water erosion on hillslopes is a worldwide environmental problem, which is a rainfall‐induced process, especially extreme rainfall. The great intensity of extreme rainfall strongly enhances the power of overland flow to detach soil and transport sediment. Plant litter is one of the most important constituents of ecosystems that often covers the soil surface and can be incorporated into topsoil. However, little attention has been paid to its effect on flow hydraulics owing to the veiled nature. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Consequently, greater runoff coefficients were found on litter incorporated slopes than those of litter covering slopes. The result is similar to the finding of Wang, Zhang, Wang, and Li () who reported that the increase in litter incorporated rate did not significantly influence infiltration. The different effects of litter covering and incorporated treatments on soil infiltration rate can be attributed to the variations in surface litter coverage and litter water repellency.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consequently, greater runoff coefficients were found on litter incorporated slopes than those of litter covering slopes. The result is similar to the finding of Wang, Zhang, Wang, and Li () who reported that the increase in litter incorporated rate did not significantly influence infiltration. The different effects of litter covering and incorporated treatments on soil infiltration rate can be attributed to the variations in surface litter coverage and litter water repellency.…”
Section: Discussionsupporting
confidence: 91%
“…The uniformity of the simulated rainfall was greater than 85%. The detailed information can be found in a previous study (Wang, Zhang, Wang, & Li, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant litter also widely exists in the topsoil of natural lands, especially in areas with high erosion intensity (Wang, Zhang, Wang, & Li, ; Liu et al, ; Figure ). Plant litter can be incorporated into the topsoil during rain splash, sediment transport, and deposition in natural circumstances (Wang et al, ; Sun, Zhang, Liu, & Luan, ).…”
Section: Introductionmentioning
confidence: 99%